The socio-demographic profile and clinical correlation of Chlamydia trachomatis among infertile women at a tertiary care center in North India - Shukla, Diksha; Kalyan, Raj Kumar; Gupta, Prashant; Venkatesh, Vimala; Agarwal, Anjoo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The frequency of Chlamydia trachomatis infection in infertile Indian women and potential risk factors associated with the infection is not well understood. To improve the primordial prevention C. trachomatis infection in developing countries, there is an urgent need to understand the prevalence of the infection among women with infertility and establish the common risk factors associated with this. This study was conducted to determine prevalence of Chlamydia trachomatis infection in infertile women attending an infertility clinic in north India and the associated socio-demographic and clinical features associated with it. Methods: Endocervical swabs, collected from 105 infertile women were tested for C. trachomatis by real time-PCR and direct gram’s stain. A detailed clinical history and examination was done on each subject during sample collection. The study group was then divided into two comparison groups and p factor was determined and factors with significant correlation were established. Results: Total 9 out of 105 infertile women visiting infertility clinic were RT-PCR positive for Chlamydia trachomatis. The socio-demographic factors that significantly correlated with Chlamydia trachomatis infection were lower age group, rural locality and illiteracy. The clinical history and examination findings that significantly correlated with the infection were past history of RTI/STI in the subject, history of RTI/STI in husband, cervical/ vaginal discharge, lower abdominal pain, burning micturition, erythema of genitalia, backache, dyspareunia and dysmenorrhea. The gram’s stain finding confirmed the active infection by presence of pus cells. Conclusions: The study concluded that the socio-demographic risk factor for Chlamydia trachomatis infection among infertile women is lower age group, rural locality and illiteracy while several clinical features that are red flags for the presence of such infection are past history of reproductive tract infection along with partner, cervical/vagina discharge, lower abdominal pain, burning micturition, erythema of genitalia, backache, dyspareunia and dysmenorrhea that should never be overseen.